Sifat-Sifat Fisik Kantong Kertas Multiwall Untuk Kemasan B3 Golongan III - Budi Utami (Jurnal Kimia dan Kemasan, 2000)
Paper sacks as a transport packaging can decrease the damage of the contains during transportation. The packaging sould conform with the design type and sould be completely tested in accordance with the requirements of the UNStandard. Experiment has been carried out to determine the specification of paper kraft which is used for paper multiwall sacks for group III dangeraous goods. The paper multiwall sacks made of three/four paper kraft liner and inner packaging LDP E film. The type of paper sacks is sewn open mouth with dimension length x width = 710 x 470 mm and 25 kg by weight. The transport simulation test of paper sacks multiwall showed that the optimum physical properties of four paper kraft liner were total weight 213, 10 gram and the thickness of LDPEfilm is 22,60 µm.